Strange objects - Crew, Gary, 1947- (New York : Simon & Schuster Books for Young Readers, 1993)
After discovering valuable relics from a seventeenth-century shipwreck, a sixteen-year-old Australian disappears under mysterious circumstances.
Booklist starred.
Publisher's Weekly.
School Library Journal.
Young Adult
Keywords: Mystery and detective stories; Mystery fiction; Australia -- Fiction; Australia -- Fiction